A case of GFAP-IgG positivity followed by anti-NMDAR encephalitis - Jia Zhang; Jing Gan; Jianjun Wang (BMC, 2022)
Abstract Background In recent years, there have been an increasing number of reports on overlapping antibodies in autoimmune encephalitis (AE). There are various types of overlapping antibodies, but the clinical significance of each type is not yet clear. Glial antibodies, such as MOG, AQP4, and especially NMDAR, can be detected in patients with AE. However, little is known about the overlapping antibodies of anti-glial fibrillary acidic protein (GFAP), and only a few case reports have described this overlap. Case presentation The patient was a 7-year-old girl with recurrent intermittent fever and seizures, and viral encephalitis was diagnosed at the beginning of the disease. She was discharged after treatment with acyclovir, high-dose immunoglobulins, and valproic acid as an antiseizure medication. Subsequently, the patient still had occasional seizures and abnormal behavior, and the anti-NMDAR antibody test was positive (1:3.2). She was treated with high-dose methylprednisolone and antiseizure therapy. Approximately half a year later, the patient experienced fever and seizures again, serum GFAP IgG was 1:100, and a head MRI indicated new lesions. Improvement was achieved after repeated high-dose methylprednisolone and continuous prednisone anti-inflammatory therapy. Conclusions Anti-NMDAR encephalitis combined with GFAP-IgG is uncommon, and repeated tests for AE-associated antibodies may be required in patients with recurrent encephalitis. Compared with cerebrospinal fluid antibody-positive children, serum GFAP IgG-positive children should be comprehensively diagnosed according to their clinical manifestations. It is worth considering whether overlapping antibody syndrome can still be an issue for patients with AE who recover and have negative antibodies after a few months if disease recurrence and new antibodies are detected.